(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Mucuna pruriens is a tropical legume native to Africa, India and Bangladesh and is widely cultivated in tropical countries. In this study, a crude methanolic extract of the leaves of M. pruriens was investigated for its chemical constituents and to explore the phenolic and flavonoid content, antioxidant, cytotoxic and antimicrobial activities using established protocols. From the ethyl acetate soluble fraction of the crude methanol extract, three known compounds namely ferulic acid (1), 2-(5-methoxy-1-benzofuran-3-yl)-N-ethylethanamine (2) and stizolamine (3) were isolated and their structures were elucidated by the analysis of NMR spectral data. The crude extract was found to possess phenolic content of 216.16 μg/g whereas the concentration of flavonoid was found to 214.8 μg/g expressed in quercetin standard. Free radicals generated through DPPH were neutralized by crude methanolic extract and the IC50 value was obtained as 19.63 μg/ml. Regression analysis during brine shrimp lethality test enumerated LC50 value of crude methanolic extract at 10.72 μg/ml and was significant compared to the positive standard. The crude methanolic extract of leaf of M. pruriens did not show any significant antimicrobial activity against the organisms used in our test. Dhaka Univ. J. Pharm. Sci. 20(1): 103-109, 2021 (June)